Methodology for determining the design radiation for a PTC heating system based on non-guaranteed days. (1st November 2018) - Ma, Minglu; Zhao, Li; Deng, Shuai; Lin, Shan; Zhang, Ying; Ni, Jiaxin; Xu, Weicong; Su, Wen
Highlights: A new method is proposed to select design radiation for a PTC based heating system. The concept of non-guaranteed days is introduced to determine the system capacity. The proposed method is more reasonable compared with the existing selection method. Abstract: Solar heating, as an alternative technology to coal-fired heating, could significantly alleviate the air pollution in China. The value of design radiation should be carefully determined when designing a solar system, as it would commonly affect the solar collector area, and then the economics and performance of the system. However, in the existing publications, most studies ignore the influence of the daily and seasonal variation of radiation, and commonly choose the fixed value of design radiation in some typical days, leading to a non-optimal performance of the system with unreasonable setting parameters. To solve this problem in the design stage, a method is proposed to determine the design radiation of a parabolic trough collector (PTC) heating system. In this method, the concept of non-guaranteed days is introduced to quickly and conveniently determine the system rated capacity. Additionally, the cost of unit heating supply is employed in this method as an optimized object of the heating system. Based on the proposed method, a case study for four typical solar radiation districts in China is conducted. Firstly, the design radiation values of each district are decided through the proposed method. Then, the relationship between non-guaranteed days and the initial investment of the system under the optimal design radiation is obtained. Finally, the economic analysis of the PTC system in Mentougou (suburbs of Beijing) is performed. This work could be a practical guide to select the design radiation for a PTC heating system without the auxiliary boiler. Moreover, the method could also be applied to more types of solar systems and regions.